Supernatant of Actinomycetes isolates with antiquorum sensing and antibiofilm activity against food spoilage bacteria - GLORIA ANNE; DIANA ELIZABETH WATURANGI (Society for Indonesian Biodiversity, 2023)
Abstract. Anne G, Waturangi DE. 2023. Supernatant of Actinomycetes isolates with antiquorum sensing and antibiofilm activity against food spoilage bacteria. Biodiversitas 24: 5189-5197. High processing food facilities occur to remove spoilage bacteria that can risk the food safety. However, bacteria can form biofilms as a survival strategy in extreme conditions. They generally use autoinducer signals in communication called quorum sensing as their modulation mechanism. Chemical agents usually treat the biofilm matrix, but side effects may occur in most cases. Therefore, it is necessary to explore natural metabolite compounds to overcome it, one of which comes from Actinomycetes. This study was conducted to determine the anti-biofilm activity of Actinomycetes supernatants, which had previously been performed using their crude extracts. The transition to using supernatant production was motivated by its higher yield and practical application. Supernatants from six Actinomycetes isolates showed positive inhibition of quorum sensing assay using Chromobacterium violaceum wild-type and mutant 026 as indicator bacteria through agar well diffusion techniques and validation assay using absorbance measurement of violacein pigment production. Based on the quantification of antibiofilm activity assay, the supernatant showed the ability to inhibit and destroy biofilm from Bacillus cereus, Bacillus subtilis, and Shewanella putrefaciens with various percentages of antibiofilm activity, with the highest antibiofilm activity of 88.34% observed for isolate SW03 specifically targeting B. subtilis biofilm destruction. It also appeared in the light microscopy and scanning electron microscopy (SEM) observation that the addition of supernatant showed inhibition and dispersion of biofilm visually compared with the untreated ones. In conclusion, Actinomycetes supernatants have the capability to be used as antibiofilm agents, therefore potential and efficient to be applied in food industry equipment and environment to increase food safety.